O problema mente-corpo na psicologia fenomenológica de Edith Stein : implicações para uma fundamentação da ciência psicológica - Moraes, Mak Alisson Borges de (2016)
Psychology is a relatively new scientific branch and still lacks consistent methodological foundation to support its investigations. Given its immaturity, this science finds difficulties to delimit its ontological status, which spawnes several epistemological and methodological misconceptions. Given this, Psychology failed to demarcate precisely its object of study, leading, thus, the emergence of numerous conceptions about the psychic, which resulted in the fragmentation of this science. In its constitution, psychological science inherited a complex philosophical problem: the mind-body issue. Therefore, to define their status, Psychology must still face this problem, seeking to elucidate what is the mind, the body and how they relate. In light of the importance of this issue to a strict demarcation of psychological object, it was sought in this research, to investigate the mind-body problem in the Phenomenological Psychology of Edith Stein (1891-1942), phenomenologist philosopher who undertook efforts for a foundation of Psychology. For that, the discussion was subsidized from the contributions of the Philosophy of Mind and the support of the phenomenological method to the mind-body problem. From there, by a qualitative bibliographical methodology, it sought to examine the problem of research through the analysis of some philosophical-psychological philosopher's works, named: "Psychic Causality” (Kausalität Psychische, 1922) and “Introduction to Philosophy" (Einführung in die Philosophie, 1920). For this investigation, it was made, without prejudice to the discussion, a terminological equivalence between the terms mind and psyche, as the philosopher used the latter to refer to the object of Psychology. It sought to examine, therefore, how Stein conceived the psyche, the body and the relationship between them. Although it wasn't the focus of the investigation, it also took into account the spiritual dimension, as the philosopher conceived the human person as consisting of three dimensions: body, psyche and spirit. Given this, Stein highlighted the causal mechanism of the psyche, which is based on the variations of the vital force that emerges from the vital sphere. In relation to the corporeal dimension, the philosopher, following the analysis of Edmund Husserl (1859-1938), highlighted the dual aspect of the body, because it is at the same time something material (Körper) and also a linving body (Leib). On the face of it, it is understood that the psyche and the body are closely connected, so that it constitutes a dual-unit which is manifested in the Leib. This understanding of the problem psyche-mind/body provides a rich analysis of this issue, enabling the overcoming of some inconsistencies of the monistic and dualistic positions. Given this, it allows a strict elucidation of the Psychology object, contributing to the foundation of this science.